Promieniowanie ultrafioletowe w leczeniu łuszczycy – przegląd badań = Ultraviolet radiation in the treatment of psoriasis - a review of research - Radzimińska, Agnieszka; Berezicka, Aneta; Weber-Rajek, Magdalena; Zimmermann, Agnieszka Anna; Bułatowicz, Irena; Strojek, Katarzyna; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Radzimińska Agnieszka, Berezicka Aneta, Weber-Rajek Magdalena, Zimmermann Agnieszka Anna, Bułatowicz Irena, Strojek Katarzyna, Goch Aleksander, Zukow Walery. Promieniowanie ultrafioletowe w leczeniu łuszczycy – przegląd badań = Ultraviolet radiation in the treatment of psoriasis - a review of research. Journal of Education, Health and Sport. 2015;5(7):553-567. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.41072 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A553-567 https://pbn.nauka.gov.pl/works/686071 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Promieniowanie ultrafioletowe w leczeniu łuszczycy – przegląd badań Ultraviolet radiation in the treatment of psoriasis - a review of research Agnieszka Radzimińska1, Aneta Berezicka2, Magdalena Weber-Rajek1, Agnieszka Anna Zimmermann3, Irena Bułatowicz1, Katarzyna Strojek1, Aleksander Goch1, Walery Zukow4 1. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Bydgoska Szkoła Wyższa, Bydgoszcz, Polska 3. Wyższa Szkoła Gospodarki, Bydgoszcz, Polska 4. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Adres do korespondencji: dr n. med. Agnieszka Radzimińska Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Marii Skłodowskiej-Curie 9, 85-094 Bydgoszcz e-mail: agnieszka.radziminska@gmail.com Streszczenie Łuszczyca jest niezakaźną, zapalną i przewlekłą chorobą skóry. Występuje u ok. 2% populacji, bez względu na wiek, płeć, w każdej szerokości geograficznej. Etiopatogeneza łuszczycy nie jest w pełni poznana, jednak uwarunkowania genetyczne tej choroby nie budzą wątpliwości. Sposób jej dziedziczenia nie jest do końca wyjaśniony. Obecnie wiele jest możliwości leczenia, jednakże leczenie zazwyczaj jest długie i musi być systematyczne. Każda łuszczyca wymaga indywidualnego postępowania terapeutycznego. Jedną ze skutecznych metod leczenie łuszczycy jest fototerapia. Wykorzystuje się do tego celu naświetlania promieniami UVB z pełnego zakresu (290-320 nm) i wąski zakres UVB (311). Stosujemy także naświetlania promieniami UVA. Skuteczność terapii zwiększa się poprzez podawanie leków uczulających na światło (terapia PUVA). Psoraleny można przyjmować doustnie w formie tabletek lub stosować zewnętrznie. Summary Psoriasis is a non-infectious, inflammable and chronic skin disease. It is appearing at 2% of the population, irrespective of the age, sex, in every latitude. The etiopathogenesis of psoriasis fully isn’t get to know, however genetic factors of this illness aren’t raising doubts. The ways for it of inheriting isn’t explained fully. At present a lot he is possibilities of the treatment, however curing usually it is long and must be systematic. Every psoriasis requires individual therapeutic proceedings. One around effective methods of psoriasis there is a light therapy. It is using to this irradiation destination with UVB rays from the full scope (290-320 nm) and UVB narrow range (311). It also apply UVA irradiation. Effectiveness of therapy is increasing by giving medicines causing an allergy in for the light (PUVA therapy). To accept psoralens it is possible orally in the form of pills or to use externally. Słowa kluczowe: promieniowanie ultrafioletowe; łuszczyca. Keywords: ultraviolet radiation; psoriasis.